Association of non-synonymous SNPs of OPN gene with litter size traits in pigs - T. Kumchoo (2018)
© Author(s) 2015. Osteopontin (OPN) gene is a secreted phosphoprotein which appears to play a key function in the conceptus implantation, placentation and maintenance of pregnancy in pigs. The objectives of this study were to verify the non-synonymous single nucleotide polymorphisms (SNPs) and their association with litter size traits in commercial Thai Large White pigs. A total of 320 Thai Large White sows were genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Three SNPs at c.425G > A, c.573T > C and c.881C > T revealed amino acid exchange rates of p.110Ala > Thr, p.159Val > Ala and p.262Pro > Ser, respectively, and were then segregated. These three SNPs were significantly associated with total number born (TNB) and number born alive (NBA) traits. No polymorphisms of the two SNP markers (c.278A > G and c.452T > G) were observed in this study. Moreover, the SNPs at c.425G > A and c.573T > C were found to be in strong linkage disequilibrium. The association of OPN with litter size emphasizes the importance of porcine OPN as a candidate gene for reproductive traits in pig breeding.